Cashiers and bisphenols: Occupational exposure and health implications in south China - Zhenni Zhu; Yanan Pan; Xiang Chen; Xin Wei; Xiaoyue Zhou; Zixiong Tang; Renli Yin; Xiaoyang Jiao; Adela Jing Li (Emerging Contaminants)
Bisphenols are ubiquitous chemicals used in various industries, raising concerns due to their potential to disrupt endocrine systems, particularly among occupational populations. This study concurrently assessed bisphenol A (BPA) and its 12 analogues in 325 urine samples from cashiers and non-cashiers residing in South China. Results revealed that BPA was the most prevalent bisphenol in urine, subsequent to bisphenol S (BPS), bisphenol F, bisphenol AF (BPAF) and bisphenol E (BPE), with detection frequencies at 60−99%. BPA exhibited the highest median concentration of 1.16 ng/mL. Urine samples from cashiers showed relatively high levels of BPA, BPS and BPE, highlighting potential occupational exposure implications. Variations in urinary bisphenol concentrations across gender and age groups were explored. Significant correlations were identified between urinary BPA and BPE, as well as BPS and BPAF, indicative of shared exposure sources and pathways. Cashiers had 1.50–13.4 times higher exposure than non-cashiers to these bisphenols. The median exposure to five bisphenols exceeded the established tolerable daily intake for BPA, set at 0.2 ng/kg bw/day, by 1.10–180 times. This study underscores the urgent need for assessing the potential health implications of bisphenol exposure, especially for high-exposure groups like cashiers, and suggests actions to reduce these risks.